CONSIDERATION OF HEAVING FORCES IN THE DESIGN OF DEEP PILE FOUNDATIONS (Uchet sil Pucheniya pri Proektirvanii Vysokikh Svainykh Rostverkov) - Chezhin,V. A. (1960)
The report contains calculations derived to determine the effect of frost heave on the design of structural foundations. Trans. of Transportnoe Stroitelstvo (USSR) n1 p19-22 Jan 58.